Andean Community: a process without real citizenship - Gortaire Morejón, Bernardo (2018)
The Andean Community faces an evident legitimacy crisis that may forecast its future collapse. Despite this, the efforts to rescue this process seem to be limited, especially those coming from the civil society. This article intends to explain this phenomenon, based on the apparent lack of a regional collective identity, by questioning the notion of an “Andean identity” and the lack of involvement of the civil society in the Andean integration process.